Distribution of chironomidae (Diptera) larvae in Hazar lake, Turkey - Tellioğlu, Ayda; Çıtıl, Cihan; Şahin, İbrahim (My University, 2008)
Density and species composition of chironomidae larvae fauna at different depths in Hazar Lake were studied. Sampling was monthly done from June 2002 to May 2003. Totaly 10 species were determined belonging to subfamilies Tanypodinae and Chironominae of family Chironomidae. Chironomus plumosus (32%) were the most abundant of chironomidae larvae and dominated at all depths. Chironomidae larvae showed considerable seasonal variations abundance. Non-parametric test of total abundance showed a significant seasonal (F= 11, P<0.01) and depth effect (F= 4, P<0.05). The quantitative data on distribution of chironomid larvae were analyzed in relation to the environmental parameters.
Keywords: Fauna; Chironomidae; Diptera; water quality; larvae; seasonal variation; Hazar Lake; depth